1998
DOI: 10.1084/jem.188.10.1895
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Influences Germinal Center Development and Antibody Production via a Contribution of C3 Complement Component

Abstract: Mice rendered deficient for interleukin (IL) 6 by gene targeting were evaluated for their response to T cell–dependent antigens. Antigen-specific immunoglobulin (Ig)M levels were unaffected whereas all IgG isotypes showed varying degrees of alteration. Germinal center reactions occurred but remained physically smaller in comparison to those in the wild-type mice. This concurred with the observations that molecules involved in initial signaling events leading to germinal center formation were not altered (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
150
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 93 publications
9
150
0
2
Order By: Relevance
“…Therefore, Foxj1 deficiency might be found in only a subset of affected individuals or mice, and may only be relevant to specific disease subtypes. Nonetheless, the present findings correlate well with the previously demonstrated importance of the NF-B pathway in the pathogeneses of several autoimmune syndromes (26); the role of IL-6 in autoreactive germinal centers (7,8); the spontaneous germinal center formation that occurs in humoral autoimmune diseases, likely in response to endogenous autoantigens (22,27); as well as the proposed utility of IL-6 blockade in the treatment of humoral autoimmune diseases like lupus (28). As such, our present findings raise the intriguing possibility that functional Foxj1 deficiency, by whatever genetic mechanism, could perhaps underlie a large proportion of autoimmune syndromes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, Foxj1 deficiency might be found in only a subset of affected individuals or mice, and may only be relevant to specific disease subtypes. Nonetheless, the present findings correlate well with the previously demonstrated importance of the NF-B pathway in the pathogeneses of several autoimmune syndromes (26); the role of IL-6 in autoreactive germinal centers (7,8); the spontaneous germinal center formation that occurs in humoral autoimmune diseases, likely in response to endogenous autoantigens (22,27); as well as the proposed utility of IL-6 blockade in the treatment of humoral autoimmune diseases like lupus (28). As such, our present findings raise the intriguing possibility that functional Foxj1 deficiency, by whatever genetic mechanism, could perhaps underlie a large proportion of autoimmune syndromes.…”
Section: Discussionsupporting
confidence: 80%
“…We find that Foxj1 modulates germinal center B cell formation in vivo via its ability to inhibit the NF-B-regulated cytokine IL-6 (7,8). Foxj1 appears to prevent inappropriate B cell responses at least in part by antagonizing NF-B target genes like IL-6, which would otherwise propagate pathogenic autoimmune responses through dysregulated B cell hyperactivation.…”
Section: Restraint Of B Cell Activation Bymentioning
confidence: 97%
See 1 more Smart Citation
“…Such wide ranges of IL-6 activities are believed to constitute an important link between adaptive and innate immunity by mediating the T cell and B cell responses involved in autoimmunity (6). In vitro studies in IL-6-knockout mice have shown a marked reduction in B cell immune responses (7), particularly reductions in the levels of IgG1, IgG2a, and IgG3 upon immunization with a T cell-dependent antigen (8), suggesting that IL-6 is central for the induction and/or maintenance of plasma cells that produce these immunoglobulin subclasses. A recent study showed that antibody production is indirectly promoted by B cell helper capabilities of CD4ϩ T cells through increased IL-21 production upon IL-6 stimulation (9).…”
mentioning
confidence: 99%
“…However, only the two-component system was strongly dependent on the endogenous IL-6 activity in vivo (Figure 8). This was expected as the complement C3 upregulation in response to an immunogen was completely absent in the IL-6 À/À mice 41,42 and was probably regulated at the level of complement C3 promoter activation. 43,44 It is known that the TAT protein can transactivate inflammatory host genes, 45 including the IL-6 gene.…”
Section: Discussionmentioning
confidence: 79%